Update on Adult Dermatomyositis - Cut Putri Hazlianda; Awalia Astarina (Indonesian Journal of Global Health Research, 2026)
Dermatomyositis is a systemic autoimmune disorder that is an inflammatory disease of the skin, muscles, and blood vessels with characteristic skin eruptions accompanied by proximal limb muscle weakness or atrophy. This condition can affect children and adults. The pathognomonic lesions are the heliotrope sign, Gottron's papule, and Gottron's sign Malignancy can occur in 10%- 20%, with nasopharyngeal cancer being the most common. Etiology and pathogenesis are autoimmune; other triggers include drugs, infection, sun exposure, and malignancy. The latest diagnosis criteria by EULAR/ACR 2017 and Sontheimer et al. can be used as a reference for diagnosis. Comprehensive management of dermatomyositis aims to decrease symptoms, increase quality of life, and early detection of malignancy. Topical therapy options for dermatomyositis are topical calcineurin inhibitors and corticosteroids. In addition, systemic therapy consists of steroid- sparing agents, antimalarials, and corticosteroids. The current treatment of dermatomyositis is the administration of intravenous Immunoglobulin (IVIG) and rituximab.